The Influence of Brebes Javanese Dialect toward Students Pronunciation of English Speech Sounds (A Case Study in SMAN 1 Brebes) - Dewi, Rahmatika; Mujiyanto, Januarius; Sukrisno, Alim (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Most English learners may have an ability to pronounce English speech sounds properly and may have problems to pronounce them. One of the influential factors is the first language interference. This study was conducted under the consideration that L1 may influence the learners pronunciation of English speech sounds. It is a qualitative study. It was aimed to investigatethe influence of BrebesJavanese Dialect toward students pronunciation of English speech sounds both positive and negative influence.The objectives of this researchare to describe the English speech sounds (vowels, consonants, diphthongs, and clusters) that are influenced by BJD and to describe the teachers roles in the development of the students pronunciation.The subjects of this study are the students in SMA N 1 Brebes. There are 20 subjects from two different classes. The data are in the form of the students voice in reading an English text twice and some isolated words once. The text is taken from the students handbook. Besides, the other supporting data are collected through other instruments. Those are questionnaire, interview, and observation.The study concludes that BJD gives negative transfer on the vowel sound [?], and diphthong [e?], [a?], [??], and [??]. However, it gives positive transfer on the consonant sounds final [b], final [d], and final [g]. It does not give any transfer to the English initial cluster /st/, /spr/, and /str/. In addition, the teachers give pronunciation practice in their teaching process.